Avaliação da cultura do milho submetida à hormesis - Sousa, Saulo Fernando Gomes de [UNESP]; Silva, Paulo Roberto Arbex [UNESP]; Benez, Sérgio Hugo [UNESP] (EIA Energy in Agriculture, 2014)
Under conservation tillage systems is critical to maintaining plant residues from previous crops on the soil surface. A technique called Hormesis aims to increase the amount of straw and also cause a delay in straw decomposition. Therefore, this study aimed to evaluate the agronomic characteristics of corn under no-tillage system subjected to Hormesis. The experiment was carried out at UNESP campus in the city of Botucatu, SP . The experimental was design in completely randomized blocks. The treatments based on the technique of Hormesis were : control (no application) , sub Gliphosate low dosage (12.5 g.ai.ha - 1 ) , sub Gliphosate average dosage (25 g. ai.ha - 1 ) , sub Gliphosate high dose (50 g. ai.ha -1 ), 2,4-D under low dose (100 g. ai.ha -1 ), 2,4-D sub average dosage (200 g. ai.ha -1 ) 2,4- D under high dosage (300 g. ai.ha -1 ) sub Verdict low dose (0.625 g. ai.ha -1 ) sub Verdict average dosage (1.25 g. ai.ha -1 ) , sub Verdict high dosage (2.5 g. ai.ha - 1 ) . In addition, the following characteristics were evaluated: plant height, first ear growth, stem diameter , ear length , number of rows per cob, cob diameter , , percentage of grains on the cob , mass of plant dry matter, and yield. The results showed that all the treatments showed no statistical difference, the maize was not affected with sub doses of herbicides applications under the field and weather conditions in which the experiment was conducted.

Nos sistemas conservacionistas de preparo do solo é fundamental a manutenção de resíduos vegetais das culturas anteriores na superfície do solo. A técnica denominada Hormesis visa aumentar a quantidade de palha e também provocar um atraso na decomposição da palha. Assim sendo o presente trabalho objetivou valiar as características agronômicas da cultura do milho em sistema de plantio direto submetida a Hormesis. O experimento foi na Faculdade de Ciências Agronômicas – UNESP/Botucatu, SP. O delineamento experimental utilizado foi o de blocos inteiramente casualizados. Os tratamentos utilizados baseados na técnica de Hormesis foram: Testemunha (sem aplicação), Gliphosate sub dosagem baixa (12,5 g.ia.ha-1 ), Gliphosate sub dosagem média (25 g.ia.ha-1 ), Gliphosate sub dosagem alta (50 g.ia.ha-1 ), 2,4-D sub dosagem baixa (100 g.ia.ha-1 ), 2,4-D sub dosagem média (200 g.ia.ha-1 ), 2,4-D sub dosagem alta (300 g.ia.ha-1 ), Verdict sub dosagem baixa (0,625 g.ia.ha-1 ), Verdict sub dosagem média (1,25 g.ia.ha- 1 ), Verdict sub dosagem alta (2,5 g.ia.ha-1 ). Foram avaliadas na cultura do milho as seguintes características agronômicas: altura de planta e de inserção da primeira espiga, diâmetro de colmo, comprimento de espiga, número de fileiras de espiga, diâmetro de espiga, peso hectolitrico, porcentagem de grãos na espiga, massa de matéria seca da planta e produtividade. Os resultados encontrados mostraram que para todos os tratamentos avaliados não houve diferença estatística, ou seja, nas condições de campo em que o experimento foi realizado, aliadas as condições climáticas ocorridas no período da realização do mesmo a cultura do milho não foi afetada com as aplicações das sub dosagens dos herbicidas.
Evaluation of maize submitted to hormesis
Keywords: No tillage; Conservation systems; Herbicides; Plantio direto; Sistemas conservacionistas; Herbicida